USE OF CAVENDISH BANANA PEEL FERMENTATION SOLUTION AND VINEGAR ON THE SHELF LIFE OF RED TILAPIA FILLETS AT LOW TEMPERATURE STORAGE BASED ON ORGANOLEPTIC CHARACTERISTICS - Evi Liviawaty; Luthfiah Al Afifah (Universitas Mataram, 2026)
Red tilapia is a fish that has the potential to be used as raw material for filets but has a drawback, namely that filets cannot maintain their freshness for a long time because filets no longer have natural defenses, making it easier for spoilage microbes to reproduce more quickly. Therefore, effective preservation techniques are needed to extend the shelf life of fish without reducing organoleptic quality. The preservation technique that can be used is low temperature preservation with a combination of natural preservatives in the form of using a fermented cavendish banana peel solution. The aim of this research is to analyze the best vinegar concentration in the fermented solution of cavendish banana peels to extend the shelf life of red tilapia fillets based on organoleptic characteristics during low temperature storage. The research method used in this research is an experimental method. Red tilapia filets were treated with soaking in a fermented cavendish banana peel solution with the addition of 0%, 0.5%, 1%, 1.5% and 2% vinegar concentrations and then stored at low temperature (5o-10oC). The results of the research showed that the administration of banana peel fermentation solution had an influence on the shelf life of red tilapia fillets as seen from organoleptic characteristics. Providing a banana peel fermentation solution with the addition of 1.5% vinegar concentration is the best treatment in maintaining the freshness of red tilapia fillets until the 11th day of cold storage.